Ethnic Identity Development, Post-Traumatic Stress Symptoms, and Relationships with Primary Caregivers: A Two-Wave Longitudinal Study among Yi Ethnic Minority Youths in Rural China School Settings - Angel Hor-Yan Lai; Hong Yao; Mengtong Chen; Wendy Suet-Yee Lau (MDPI AG, 2022)
Background. This study examined the effects of post-traumatic stress symptoms and child-primary caregiver relationships on the ethnic identity of Yi ethnic minority adolescents (n = 550; aged 13-18) in rural China over one school year. The moderating effect of caregivers' relationships over time and ethnic identity, and post-traumatic stress and ethnic identity, were investigated. Methods. Participants completed two waves of the survey. Longitudinal multilevel modeling was used. Results. (1) Ethnic identity exploration increased over time, while ethnic identity commitment remained stable. (2) Post-traumatic stress symptoms led to high levels of ethnic identity exploration and commitment. (3) Participants with distinct caregivers' relationship patterns, i.e., secured, optimal, deprived, and disengaged, differed in their ethnic identity exploration scores, but not in ethnic identity commitment. (4) While the secured group scored highest in their ethnic identity development over time, youths who felt disengaged with their caregivers showed the fastest rate of positive change in their ethnic identity exploration. (5) Having a secured caregivers' relationship weakened the effect of post-traumatic stress on ethnic identity exploration. Conclusion. Practical implications for the meaning of ethnic identity exploration, the promoting effect of caregivers' relationships, and the negative impact of post-traumatic stress among ethnic minority youths were discussed. Future research directions were also proposed.